Penerapan Terapi Bermain Meniup Baling-Baling Pada Anak Sekolah Dengan DBD Terhadap Penurunan Intensitas Nyeri Setelah Pemasangan Infus - Ari Andrean; Ketut Suryani; Maria Tarisia Rini (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The process of installing an IV will cause pain which can disturb the child. Pain is an unpleasant event in individuals that can cause sufferers to feel sick. Apart from that, there will be changes in vital signs such as increased pulse rate, blood pressure and breathing, so it will be an unpleasant experience for the child. Pain from installing IV fluids in children can be minimized with non-pharmacological measures which aim to manage pain, namely with relaxation therapy, playing blowing propellers. To determine the effectiveness of blowing propeller play therapy on reducing pain in children when installing an IV. This research uses a descriptive case study with a nursing process approach with a case study design of 3 respondents, with a paper propeller game and the Wong Baker pain scale. The data collection process was carried out on respondents by blowing a propeller for 5 minutes on each respondent. The research results showed that play therapy blowing propellers was effective in reducing the intensity of pain in children after installing an IV as proven in An. B from scale 7 to scale 4, An. Z from scale 8 to scale 6, and An. R from scale 7 to scale 5. The results of the research are that it is hoped that propeller blowing therapy can reduce the intensity of pain in children after infusion.